2021
DOI: 10.1021/acs.est.1c03457
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Seleno-l-Methionine Causes Alterations in Neurotransmitters, Ultrastructure of the Brain, and Behaviors in Zebrafish (Danio rerio)

Abstract: Elevated concentrations of dietary selenium (Se) cause abnormalities and extirpation of fish inhabiting in Se-contaminated environments. However, its effect on fish behavior and the underlying mechanisms remain largely unknown. In this study, two-month-old zebrafish (Danio rerio) was fed seleno-l-methionine (Se-Met) at environmentally relevant concentrations (i.e., control (2.61), low (5.43), medium (12.16), and high (34.61) μg Se/g dry weight (dw), respectively, corresponding to the C, L, M, and H treatments)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 77 publications
0
15
1
Order By: Relevance
“…40−42 It is likely that the fish with reduced growth might be more vulnerable to predation and could be extirpated from the Se-contaminated aquatic environments. 2 Though many studies 43,44 and our recent companion paper 32 have shown that Se at essential levels might be beneficial to fish growth, stimulated growth was not observed in the Se-Met treated Oryzias latipes in this study.…”
Section: ■ Results and Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…40−42 It is likely that the fish with reduced growth might be more vulnerable to predation and could be extirpated from the Se-contaminated aquatic environments. 2 Though many studies 43,44 and our recent companion paper 32 have shown that Se at essential levels might be beneficial to fish growth, stimulated growth was not observed in the Se-Met treated Oryzias latipes in this study.…”
Section: ■ Results and Discussioncontrasting
confidence: 59%
“…Similarly, decreased body weight, fork length, and condition factor have been observed in the Sacramento splittail ( Pogonichthys macrolepidotus ), rainbow trout ( Oncorhynchus mykiss ), and white sturgeon ( Acipenser transmontanus ) fed the Se-Met enriched diet for over 2 months, implying the deleterious effects of excess Se on fish growth. It is likely that the fish with reduced growth might be more vulnerable to predation and could be extirpated from the Se-contaminated aquatic environments . Though many studies , and our recent companion paper have shown that Se at essential levels might be beneficial to fish growth, stimulated growth was not observed in the Se-Met treated Oryzias latipes in this study. Since the Japanese medaka used were adults, they might have passed the ages for fast growth which normally occurs in juvenile fish .…”
Section: Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Conclusive evidence for its toxicity at elevated concentrations to aquatic organisms has been obtained from the two heavily Se-contaminated aquatic ecosystems, i.e., the Belews Lake and Kesterson Reservoir, which have witnessed the extinction of a number of apex predatory species ( sh and birds) in the aquatic food chain (Hamilton, 2004;Lemly, 2004). Meanwhile, laboratory experiments have documented a variety of adverse effects of Se in different aquatic organisms, including teratogenicity (Wang et al, 2020), neurotoxicity (Li et al, 2021), oxidative stress (Janz et al, 2010), the composition of microbial community (Liu et al, 2022), etc.…”
Section: Introductionmentioning
confidence: 99%